Bibliometric Analysis of Parents' Health Belief Model Study of Vaccine Administration of Covid-19 - Handayani, Eka Wuri; Perwitasari, Dyah Aryani; Dermawan Purba, Fredrick; Irham, Lalu Muhammad (Universitas Muhammadiyah Surakarta, 2024)
A bibliometric analysis was conducted to assess the interest and significance of research on the Health Belief Model. The bibliographical information provides insights into the Health Belief Model concerning parents of children receiving the COVID-19 vaccine. As of January 25, 2023, data for the study were obtained from the Scopus database. Our analysis identified 876 articles with the keywords: Health Belief Model, Parents, and COVID-19 Vaccine. Articles were exclusively selected in English, and the analysis was performed using the R Studio 4.2.2 application for Bibliometric Analysis. China hosts the top five most productive authors, with Peking University contributing the highest number of articles (66 in total). The Vaccines Journal emerges as the primary publisher, while the majority of collaborative research on COVID-19 involves authors from the United States. Frequently used keywords include Human, Female, Male, Adult, COVID-19, and Article. The increasing trend in Health Belief Model articles related to the COVID-19 vaccine from 2020 to 2023 underscores the widespread interest in and appeal of this subject for discussion. Given the study's limitation, including only publications released before January 25, 2023, it is plausible that some more recent publications were unintentionally overlooked.